Clinical application of multicolor imaging in Leber hereditary optic neuropathy - Cheng, Yufang; He, Lu; Miao, Qingmei; Wang, Wenyu; Yuan, Jiajia; Chen, Changzheng (Frontiers in Neurology, 2022)
Purpose: To characterize features of retinal never fiber in Leber Hereditary Optic Neuropathy (LHON) using multicolor (MC) imaging and color fundus photography (CFP). Methods: Ninety-twoeyes of LHON patients underwent MC imaging, optic disc spectral domain optical coherence tomography (SD-OCT) and CFP. Two independent observers graded RNFL visibility scores and two other experts determined never fiber bundle defects from four-quadrant readings. CFP, standard MC, infrared reflectance (IR), green reflectance (GR), blue reflectance (BR) and green-blue–enhanced (BG) imaging were compared. Results: Agreement on never fiber bundle defects was substantial for CFP, standard MC, GR, BR and BG images relative to IR. It was showed that BR (2.71±0.55) had the best mean RNFL visibility score, BG (2.69±0.52), GR (2.69±0.56), standard MC (2.04±0.79), CFP (1.80±0.82) and IR (0.45±0.59) followed. Agreement on temporal area defects was relatively improved. Youden indices for CFP (78.21%), standard MC (84.48%), GR (90.92%), BR (89.64%) and BG (90.99%) indicated good detection of defects in papillomacular bundle (PMB)/ high suspicion of LHON patients, particularly for BG and GR. According to proportion of never fiber bundle defects, standard MC, GR, BR and BG can roughly determine LHON clinical stage, especially in subacute and chronic stages, and standard MC is superior for LHON patients of all stages. The stage judged by MC was consistent with the course inferred by pRNFL thickness. Conclusions: As an adjunct to SD-OCT, the MC image, particularly the GR and BG can delineate RNFL more effectively than CFP. The MC image may be a useful adjunct to OCT for detecting or monitoring never fiber bundle defects, providing an inexpensive and rapid methods that can quickly identify patients with high suspicion of LHON.